The Impact of the Work Tools and the Physical Work Environment on The Degree of Job Satisfaction among Workers In the Governmental Agencies in Cairo and Giza Governments - Ahmed, Abdelnaser Mohamed Sayed (The Arab Journal of Administration, 2024)
The problem of the study was to determine the impact of work tools and the physical work environment on the degree of job satisfaction among workers in governmental institutions. The study is of the type of descriptive / analytical studies. The social survey method was guided by the sample. In order to answer the following study questions: What are the characteristics of the work tools available to employees in governmental institutions? What are the physical aspects of the employee’s room available to workers in governmental institutions? Also, to test the validity of the following hypotheses: There is a positive direct relationship between the characteristics of work tools and the degree of job satisfaction among workers in governmental institutions. There is a positive direct relationship between the physical aspects of work room and the degree of job satisfaction for workers in governmental institutions. Data were collected from a non - random sample (its size 42) from some of the workers in some governmental institutions located in the governorates of Cairo and Giza. The data was collected by a questionnaire that included a set of questions related to work tools and work room, and by a scale of job satisfaction for workers in organizations. Among the most important results of the study: answering the study’s questions, and the validity of the study’s hypotheses.